126 Determining the Minimally Clinical Important Difference in Pain, Quality of Life, and Disability for Spinal Cord Stimulation for Failed Neck and Failed Back Syndromes. (August 2015) - Paul, Alexandra Rose; Kumar, Vignessh; Roth, Steven G.; Gooch, M. Reid; Pilitsis, Julie G.
Abstract : INTRODUCTION: With rising health care costs, clinical outcome data are becoming increasingly important. The concept of minimally clinical important difference (MCID) has been shown to be effective in spine surgery to differentiate between clinically insignificant and significant improvements and to measure the patient's perspective of quality of life and disability. We sought to determine the MCID for spinal cord stimulation (SCS) therapy for failed neck and back syndromes, which has not been established to date. METHODS: Preoperative and 6-month outcomes were assessed prospectively, including the Oswestry Disability Index (ODI), Beck Depression Inventory (BDI), and Visual Analogue Scale (VAS) questionnaires. Patients were asked by a blinded investigator: (1) are they satisfied with SCS therapy and (2) would they have the surgery again? Four methods of calculating the MCID were used, including the average change approach, the minimum detectable change approach, the change difference, and the receiver operating characteristic approach. RESULTS: Forty-eight patients who underwent SCS placement from 2012 to 2014 were prospectively reviewed. Thirty-five (73%) patients stated they were satisfied with SCS therapy and they would have the surgery again. Satisfied patients had an average improvement of 2.9 points on the VAS and 11.5 points on the ODI at 6 months compared with an average decline of 0.78 points on the VAS and 1.8 points on ODI in the patients who were not satisfied with SCS therapy ( P = .005, P = .06). The 4 calculation methods yielded a range of outcome scores (ODI 8.2-13.3, BDI 3.2-7, McGill 0.3-1.3, and VAS 1.2-3.7). CONCLUSION: The MCID for SCS placement was calculated by using 4 methods. The results are similar to calculations for the MCID for traditional surgical procedures done for pain. Our results suggest that an improvement of 1.2 to 3.7 points on the VAS scale and 8.2 to 13.3 points on the ODI is clinically meaningful to the patient. Further defining the MCID for SCS therapy will remain of utmost importance in order to justify the cost of the procedure.